SURVIVAL AND COMPLICATIONS ASSOCIATED WITH UNCONVENTIONAL ENDOPROSTHESIS RECONSTRUCTIONS FOR PRIMARY BONE TUMORS AND BONE METASTASES - DANIEL CÉSAR SEGUEL REBOLLEDO; RODRIGO DA SILVA CORDEIRO; ANDRÉ MATHIAS BAPTISTA; LUIZ FILIPE MARQUES CORREIA; RICARDO PIETROBON; OLAVO PIRES DE CAMARGO (Acta Ortopédica Brasileira)
ABSTRACT Objective: To evaluate the survival and complications associated with unconventional stent reconstructions for bone and soft tissue tumors. Methods: We retrospectively extracted data from the ICESP (Instituto do Cancer do Estado de São Paulo) registry system to evaluate postoperative complications, including thrombosis, amputation, infection, tumor recurrence, and death. We also assessed time until complications and reoperations, as well as survival. Results: We evaluated 108 patients who underwent unconventional stent reconstruction surgeries for bone tumors. There were significant associations between smoking and tumor recurrence, and between type of cancer, patient functionality, hypertension, and the occurrence of postoperative complications, presence of comorbidities, and death after surgery. Patients with soft tissue tumors and those unable to perform normal activities were at risk of earlier complications. Conclusion: Type of cancer, patient functionality, presence of comorbidities, stent location, and exposure to chemotherapy or radiotherapy are important risk factors associated with complications and survival after unconventional stent reconstruction surgeries. Level of Evidence IV, case series, retrospective study.